Myocardial infarction or myocarditis? A case report and review of a myocardial adverse event associated with mRNA vaccine - Badaró, Roberto; Novaes, Gustavo; Andrade, Ana Cristina; de Araujo Neto, Cesar Augusto; Machado, Bruna Aparecida; Barbosa, Josiane Dantas Viana; Soares, Milena Botelho Pereira (Frontiers in Medicine, 2023)
A 23-year-old man with chest pain started eight hours after his first Pfizer-BioNTech COVID-19 vaccination. ECG showed sinus tachycardia with ST-segment elevation in D1, AVL, V5 and V6 compatible with acute subepicardial myocardial damage. However, cardiac MRI documented myocardial fibrosis, with cardiac late enhancement non-ischemic pattern with diffuse edema. He had no other symptoms to suggest another etiology than the vaccination. The patient had a history of Wolf-Parkinson White that was corrected with ablation when he was 11 years-old. This report calls the attention for myocardial adverse reaction risk for mRNA COVID-19 vaccines for people with a previous cardiac disease history.